Institutional and Public Communication on the Russian-Ukrainian War: Between Journalism and Documentation - Lesia, Lysenko (Asian Journal of Interdisciplinary Research, 2026)
The Russian-Ukrainian war has impacted the field of war journalism, in which user-generated audiovisual content has become an important tool for capturing, interpreting, and disseminating the experience of war. The study aimed to study the cultural and historical aspects of military journalism in Ukraine based on a qualitative analysis of audiovisual content. At the same time, the study is based on a qualitative content analysis of video materials shared on social networks (YouTube, TikTok, Twitter (X)) by civilians, military personnel and public activists. For this purpose, an intersectoral approach was used, which made it possible to identify the main differences in the methods of presenting military events and their cultural and historical significance. The analysis showed that the user narratives reflected the themes of patriotism, historical memory, solidarity, humor and gender aspects. It was found that civilians most often focused on personal trauma and loss, the military on collective resilience and heroism, while activists emphasized international support and cultural mobilization. The symbols that appeared in the video (positive images, city ruins, everyday objects, images of defenders) formed a new level of cultural representation of the war. Thus, the article demonstrated that UGC is not just an alternative source of information, but an important cultural resource that influences the development of military journalism and contributes to the construction of Ukrainian identity.